Material Dinding Kedap Suara dengan Memanfaatkan Pelepah Pisang Raja Susu - Suharyani, Suharyani; , Dr. Ir. Dhani Mutiari, MT; , Dr. Moch. Solikin (2016)
Noise becomes a very important issue to reach a level of comfort in the room. The choice of material is less precise also be the cause of the noise. The sound reduction may occur depending on the type of material absorption. Several previous studies have examined the multiple alternative materials soundproof walls that have characteristics similar to the dried banana stems, as examples of which are: coconut husks, rice husks and waste wood saws. Porous sound absorbing element has a characteristic absorption more efficient. Wall thickness and spacing layer also specifies the optimization level of damping of the sound. This study examined the waste banana stalk as soundproof partition walls. Banana type used in this research is the plantain milk is considered cheaper and more widely available around the home environment. The method used to determine the value of sound reduction and absorption coefficient is making some kind of woven from banana stems and dried. Twisted banana stems, dried and made of webbing. Matting is then given a finishing plywood sheeting, to be used as a partition wall. This research material absorbency test performed in the laboratory of acoustic and performed tensile test to determine the tensile strength of the material. Data analysis using Realtime Software Analyzer (RTA). Material acoustic panel has the ability to absorb sound well at a frequency of 1000 Hz. Absorption coefficient is most effective on woven diagonally, at a frequency of 1000 Hz (α = 0.43), frequency of 2000 Hz (α = 0.27) and a frequency of 4000 Hz (α = 0.32). Pattern woven with the composition variation P312 (tightly woven diagonal, cross, straight) is most effective in the absorption of the sound. At frequencies 1000 HZ (α = 0.46), frequency of 2000 Hz (α = 0.87) and a frequency of 4000 Hz (α = 0.32).